Revolução feminina silenciosa : a universitária católica recifense e a construção de uma nova identidade psicossocial e ético-religiosa - Albuquerque, Janice Marie Smrekar (2007)
The principal objective of this dissertation is to detect and analyse the construction of a new psicological, social and ethical religious identity of the female catholic university student in Recife. By means of her life style and conceptual representations, she evidences a confrontation between the Catholic Church´s magistery and the challenges she faces in today´s world. This academic work proposes to indicate the Catholic Church´s principal orientations about women elaborated since Vatican Council II, to identify problemas faced by women referring to corporality, sexuality and reproductive health and to confront the Church´s teachings with the living spirituality of the women as they face challenges in the modern world. Gender hermeneutics is used as the interpretative instrument of analysis of the Church´s magistery and the results of the reseach. A characterization of the two Institutions of Superior Education, the Catholic University of Pernambuco (CATÒLICA) and the Frassinetti College of Recife (FAFIRE), where the survey was conducted, has been elaborated, as well as the verification of the catholic female students´ construction of their new psychological, social and ethical-religious identity, and the day by day living of their feminine spirituality. The methodology of the research involves a field survey of 178 catholic women, from the two educational institutions, by means of a questionnaire with 31 closed questions. The conclusions are a result of quantitative and qualitative analyses, which will later be socialized with the educational institutions and other institutions and councils interested in this theme. The results of the research are the identification of the psycological, social, ethical, religious and cultural elements constituting the new identity of the female catholic university student in Recife as she faces contemporary challenges in her relation with the Catholic Church magistery. It is hoped that these results will contribute to a reflection about possible integrative educational and pastoral strategies to help catholic women live their new identity in this complex world.